Предмет: Алгебра,
автор: dashabarbisid
Реши уравнение (Х-3)(х+5)-(х-0,4)(х-3) =0
Ответы
Автор ответа:
1
Ответ:
х = 3,5
Объяснение:
2(3х²-5x+1)-3(2x²-4x+3) = 0
6х² - 10x + 2 - 6x² + 12x - 9 = 0
2х - 7 = 0
2х = 7 х = 7/2 х = 3,5
Автор ответа:
0
Ответ:
x=3
Объяснение:
x(x+5)-3(x+5)-(x(x-3)-0,4(x-3))=0;
x²+5x-3x-15-(x²-3x-0,4x+1,2)=0
x²+2x-15-x²+3,4x-1,2=0
5,4x-16,2=0
5,4x=16,2
x=16,2/5,4=162/54=3
Похожие вопросы
Предмет: Английский язык,
автор: 3636zara
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Английский язык,
автор: stanislava017
Предмет: Русский язык,
автор: olgamarorozova
Предмет: Английский язык,
автор: katya292960